Determinants of cervical cancer screening service utilization among women attending healthcare services in Amhara region referral hospitals: a case-control study - Temesgen Dessalegne Legasu; Kibir Temesgen; Zenebe Tefera Ayele; Moges Sisay Chekole; Fekade Demeke Bayou; Jemberu Chane Fetene; Abebe Tadesse Tibebu; Birhan Tsegaw Taye; Mohammed Ahmed Ali (BMC, 2022)
Abstract Background Cervical cancer is the second leading cause of cancer-related death and one of the top 20 causes of death among women in Ethiopia. Cervical cancer screening service has a vital value to reduce morbidity and mortality. Even though cervical cancer screening service utilization in Ethiopia is unacceptably low, its determinant factors were not well studied in the study area. Hence, this study was aimed at filling this information gap. This study aimed to identify determinants of cervical cancer screening service utilization among women attending healthcare services in Amhara region referral hospitals, Ethiopia. Methods Hospital-based case-control study was conducted among 441 women (147 cases and 294 controls) from May to July 2021. Cases were included consecutively and controls were selected using a systematic random sampling technique from the randomly selected hospitals. A pretested interviewer-administered questionnaire was used to collect the data from respondents. The data were entered into Epi data version 4.6 and exported to SPSS version 25 for analysis. Bivariable and multivariable logistic regression analysis was employed. Adjusted odds ratio with its 95% confidence interval and p value < 0.05 were used to estimate the strength and significance of the association. Result A total of 147 cases and 294 controls were enrolled in this study. Women with 30-39 years-old [AOR = 2.3; 95% CI 1.21, 4.68] and 40-49 years-old [AOR = 4.4 95% CI 1.97, 10.12], urban residence [AOR = 2.6; 95% CI 1.36, 5.21], secondary education [AOR = 4.4; 95% CI 2.18, 8.87] and diploma and above [AOR = 2.0; 95% CI: 1.05, 4.59], ever gave birth [AOR = 9.4; 95% CI 4.92, 18.26], having multiple sexual partners [AOR = 2.8; 95% CI 1.60, 5.03], good knowledge towards cervical cancer screening [AOR = 3.6; 95% CI 2.07, 6.43] and positive attitude on cervical cancer screening [AOR = 2.0, 95% CI 1.20, 3.70] were significant determinants of cervical cancer screening service utilization. Conclusion In this study, age (30-39 and 40-49), urban residence, secondary education, ever gave birth, good knowledge of cervical cancer screening, positive attitude towards cervical cancer screening, and having multiple sexual partners were significant determinants of cervical cancer screening service utilization. There is a need to strengthen the policy and health education on safe sexual practices and healthy lifestyles through information dissemination and communication to scale up screening service utilization.